Peer acceptance and the development of emotional and behavioural problems: Results from a preventive intervention study. (November 2015) - Menting, Barbara; Koot, Hans; van Lier, Pol
Difficulties in peer acceptance during elementary school have been associated with emotional and behavioural problems. This study used a randomized controlled intervention design to test whether improvements in peer acceptance mediated reduced rates of emotional and behavioural problems in intervention compared to control-group children. A total of 615 elementary school children in the Netherlands were followed annually from kindergarten through second grade. Intervention children showed reductions in emotional and behavioural problems, and improved peer acceptance compared to controls. Improved peer acceptance mediated reductions in emotional and behavioural problem development. However, this mediation pathway held only for boys with low receptive vocabulary skills. These results indicate poor peer acceptance as a common underlying factor in emotional and behavioural problem development, particularly for children who are at risk for developing problems.